Environmental assessment for sustainable development (Copenhagen, Denmark, 1999)
Guidance on environmental assessment up to the approval stage programme support. Guidance on environmental assessment after the approval stage of sector programme support. Further guidance the environmental assessment process. Sectoral guidance notes.
Đánh giá tác động môi trường và rủi ro sinh thái,Đánh giá tác động môi trường
Keywords: Environmental impact analysis